Kualitas Pengungkapan SDGs: Apakah Berpengaruh terhadap Kinerja Keuangan Perusahaan Sektor Energi dan Bahan Baku di Indonesia? - Nadhila Putri Arifianti; Luky Patricia Widianingsih (Universitas Muhammadiyah Malang, 2023)
Purpose: This study aims to examine the effect of the quality of the disclosure of SDGs in the Sustainability Report on financial performance through ROA and ROE. Methodology/approach: The population of this study are companies listed on the IDX in the Energy Sector and Basic Materials Sector (Metal & Mineral Industry). This study uses historical data and content analysis then multiple linear regression analysis. The measurements used are very specific so 86 observational data from 37 companies. Findings: The results of the study show that the quality of SDGs disclosure does not affect ROA and ROE. Further exploration of the content analysis found that the contribution to achieving the SDGs in sectors was only dominant in the Economic pillar. Practical implications: The company is starting initiatives to carry out activities that support the SDGs so they can present complete and comprehensive information, not only one pillar. Management focuses on more exploratory and quantitative disclosures. Originality/value: Measurement of the quality of SDGs disclosure uses a comprehensive matrix associated with the 2018 GRI Standards and then an empirical study on financial performance. Complemented research by further exploring the quality of SDGs disclosure from the content analysis results.